THE EFFECTIVENESS OF THE USE OF MANAGEMENT INFORMATION SYSTEMS AND HOSPITAL FACILITIES IN IMPROVING SERVICES IN THE OUTPATIENT UNIT OF LINDIMARA CHRISTIAN HOSPITAL - Yuliyanti Konga Wandal (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Hospitals as health service institutions are required to manage resources and service processes optimally in order to meet the expectations of patients and the wider community in providing fast, precise and accurate services. Hospital Management Information System (SIMRS) is a computer system that integrates the entire flow of health service business processes, from administration to medical services, with the aim of providing fast and accurate information. The purpose of this study was to evaluate the effectiveness of the implementation of the Management Information System and support for health facilities that have a positive impact on improving services at the Outpatient Unit of Lindimara Christian Hospital. With the Correlation method and filling out the Questionnaire to respondents, it is hoped that the implementation of SIMRS and the Health Facilities used will prove effective in improving health services in the Outpatient Unit of Lindimara Christian Hospital through automation of service flows, development of business process management, improvement of human resource quality, and utilization of appropriate technology.